Isovolemic filter-based therapeutic plasma-exchange with fresh frozen plasma is associated with minimal thromboelastometric changes in noncoagulopathic patients. Issue 3 (April 2021) - Popescu, Mihai; Marcu, Alexandra; Dinca, Alexandru; Tanase, Andreea; Tomescu, Dana
Abstract : N/A: The aim of this study was to assess the effects of isovolemic therapeutic plasma-exchange using fresh frozen plasma on coagulations parameters assessed by standard coagulation tests and rotational thromboelastometry in noncoagulopathic patients. Twenty patients who underwent isovolemic filter-based therapeutic plasma-exchange of approximately 1.5 plasma volume per session were included in the current study. Standard coagulation tests and rotational thromboelastometry (ExTEM, InTEM, FibTEM and ApTEM) were performed 30 min before and after the procedure. Isovolemic therapeutic plasma-exchange was associated with decreased fibrinogen levels ( P  = 0.01). Thromboelastometric assay demonstrated an increased clotting time in both ExTEM ( P  = 0.03) and InTEM ( P  = 0.01) and a decreased thrombodynamic potential index in ExTEM ( P  = 0.03). No significant difference in FibTEM maximum clot firmness was recorded ( P  = 0.41). Therapeutic plasma-exchange in noncoagulopathic patients is associated with minimal changes in thromboelastometric parameters, mainly by an increase in clotting time in both intrinsic and extrinsic pathways.